Petrous Apex Pneumatization: Influence on Postoperative Cerebellopontine Angle Tumor Cerebrospinal Fluid Fistula. (September 2018) - Shew, Matthew; Muelleman, Thomas; Harris, Michael; Li, Michael; Sykes, Kevin; Staecker, Hinrich; Adunka, Oliver Fr; Lin, James
Objective: Multiple investigators have sought to identify risk factors for cerebrospinal fluid (CSF) leak following cerebellopontine angle (CPA) tumor resection. We evaluated whether pneumatization of the petrous apex (PA) is a risk factor for CSF fistula. Method: We conducted a retrospective chart review at 2 major tertiary academic institutions undergoing CPA tumor resection and analyzed their respective head or temporal computed tomography (CT) scans if available. Results: A total of 91 cases were identified; 51 (64%) demonstrated PA pneumatization, and a total of 17 CSF leaks were identified. We discovered higher rates of CSF leak (25.0% vs 13.7%; P = .273) and CSF rhinorrhea (15.0% vs 5.9%; P = .174) in patients with PA pneumatization compared to those without PA pneumatization. Conclusions: Isolated PA pneumatization may be a risk factor and communication pathway for CSF fistula. Further studies will need to be broadened across multiple institutions to draw any additional and stronger conclusions.